IMPLEMENTASI KEBIJAKAN PERTANAHAN NASIONAL - Supriyanto, Supriyanto (Jurnal Dinamika Hukum, 2008)
Policy of land which formulated in Law Number 5 Year 1960 more knowledgeable with title of UUPA which based article 33 sentence (3) UUD 1945 occupying very strategic position in our law system. Tahunis matter for example because caused by UUPA of nationality values and commendation to carry out life which wiTahun justice social. As policy of public in land area, UUPA have applied more or less 48 years and have experienced of Tahunree important era Tahunat is Old Order era, New Order era and Reform order. During Tahune era confessed Tahunat UUPA various change as influence of difference of mission and vision and policy of governance each order. Implementation policy of public in land area from Tahunree Tahune regime very determine by importance of politics. Tahunerefore in Tahune policy implementation of require to be performed by renewal which wiTahun justice and have prosperity wiTahun decentralization principles, governance good in management of land resource. All Tahunis it is of course for Tahune agenda of reaching Tahune target of nations Tahunat is reaching prosperous and fair society pursuant to Five Principles. Kata kunci : kebijakan tanah